Low fat goat meat sausage with chitosan-glucose Maillard reaction product: impact on quality and shelf life - Deborah Silva do AMARAL (Food Science and Technology)
Abstract Low fat fresh goat sausages based on chitosan (LMWC) and derivative chitosan (LMWC-Glc) were developed aiming to produce a functional food product evaluating the effect of inclusion of these compounds on quality, stability and shelf life. Goat sausages (10% pork fat) were formulated with 2% (w/w) of LMWC or LMWC-Glc and stored at 4 °C during 21 days. Results indicated that incorporation of LMWC-Glc and LMWC is technologically feasible, originating a potential functional product with low fat content, besides the positive impact on microbial safety. The modified LMWC (towards better solubility and lower adstringency) incorporated at 2% as functional ingredient maintained positive effect on antimicrobial, nutrional, textural and sensory performance. The results also proved that derivative chitosan may also be a promising strategy for improving the quality and extending the shelf life of low fat goat sausage.